Low-error Fixed-Width Booth Multiplier using Approximation of Carry Function - Ganjikunta Ganesh Kumar; Sibghatullah Inyatullah Khan; G Prasad Acharya; Shravan Kumar S M (Journal of Applied Science and Engineering, 2025)
This paper introduces an innovative solution for increasing precision of fixed-width radix-4 Booth multipliers through variable error compensation functions that leverage Approximation of Carry Function (ACF). Error compensation mechanisms typically comprise two carries-ideal and base carry functions–strategically chosen to minimize mean error. We present three distinct methods-ACF-1, ACF-2, and ACF-3—each employing fixed base values with varying column information (w) and bit lengths (N). Comparative analyses against recent studies demonstrate that our proposed fixed-width Booth multiplier using ACF-1 stands out in terms of accuracy and efficiency tradeoffs.